Chemical fundamentals of the action of radicals in the body / Fundamentos químicos da ação dos radicais no organismo - Amanda Lima Cunha; Karlliane Silva Moura; James Cleudson Barbosa; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2016)
In recent years, some conditions have been challenging the scientific and health sector. These pathologies are developed by the so-called free radicals, which are highly reactive molecules or atoms and have their electronic structure in an unpaired electron. Free radicals are formed from the breakdown of a covalent bond, where each "part" is shared with an electron or may be formed by a redox reaction, where only one electron is transferred. In the human body, the radicals are produced endogenously and exogenously. In endogenously are produced by the metabolism of oxygen, generating the so-called reactive oxygen species metabolism. Exogenous sources are air pollution, ultraviolet and X - ray, cigarettes, alcohol, stress and high consumption of saturated fats. The radicals deriving from reacting with oxygen metabolism of cells by altering their genetic code DNA and producing an abnormal cell proliferation. These atoms or molecules react with other cells, triggering the known oxidative stress. Hence, the objective was to explain the reaction of the radicals in the human body. The methodology used was based on literature searche , which was identified scientific articles dealing with the action of radicals and their chemical foundations . From the survey the radical species of oxygen metabolism (superoxide, hydroxyl, etc. hidroperoxila ) , and the effects of each radical species in the body was identified . Therefore, the present study was to focus reporting the harmful effects of radicals in the human body.